African Group of Negotiators submissions play significant role in achieving the Koronivia Joint Work on Agriculture - CGIAR Research Program on Climate Change, Agriculture and Food Security (2017)
The African Group of Negotiators (AGN) submissions significantly contributed to Koronivia Joint Work on Agriculture at COP23. Since 2012, CCAFS East Africa has continuously supported agriculture and climate change negotiators and experts from Africa to prepare submissions for UNFCCC negotiations. More recently, the roadmap developed during SBSTA48 builds heavily on AGN submission. Over 10 technical working sessions have been convened with AGN, where CCAFS and CGIAR knowledge outputs provided scientific evidence to articulate vulnerability of African agriculture to climate change.